The Use of Adipose-Derived Stem Cells in Selected Skin Diseases (Vitiligo, Alopecia, and Nonhealing Wounds) - Agnieszka Owczarczyk-Saczonek; Anna Wociór; Waldemar Placek; Wojciech Maksymowicz; Joanna Wojtkiewicz (Stem Cells International)
The promising results derived from the use of adipose-derived stem cells (ADSCs) in many diseases are a subject of observation in preclinical studies. ADSCs seem to be the ideal cell population for the use in regenerative medicine due to their easy isolation, nonimmunogenic properties, multipotential nature, possibilities for differentiation into various cell lines, and potential for angiogenesis. This article reviews the current data on the use of ADSCs in the treatment of vitiligo, various types of hair loss, and the healing of chronic wounds.